PROCESSING DENTURES USING A MICROWAVE TECHNIQUE - (:unkn) unknown (BLACKWELL SCIENCE LTD, 1994)
In this research the technique of curing denture base acrylic resins by microwave energy was investigated with respect to polymerization method, hardness, mechanical and physical properties. Twenty-one different polymerization methods were used by varying radiation power and curing time. The Vickers hardness test was applied to the samples which were polymerized. The average value was found to be 22.46 VHN (Vicker hardness number), that is, almost the same as conventionally cured acrylic. The recommended polymerization method of curing acrylic was 3 min at 550 W in a microwave oven. Mechanical and physical tests were applied to the samples which were cured by the recommended polymerization method. The average transverse load to fracture value was found to be 7.6 kg, and the transverse deflection value was 1.5 mm at 3500 g, and 2.9 mm at 5000 g. Water sorption of acrylic resin cured by microwave energy was 0.72 mg cm-2 and the solubility rate in water was 0.038 mg cm-2. Results conformed with the ADA specification. The findings showed that acrylic resin cured by microwave energy is more resistant to mechanical failure than conventionally cured acrylic and this technique can safely be applied to the production of denture bases.
Keywords: ACRYLIC RESINS